SEJARAH PEMERINTAHAN DATUK LAKSAMANA IV BUKIT BATU TAHUN 1908-1928 - Ujang Sudrajat; Prof.Dr.Isjoni, M.Si '; Bunari, S.Pd, M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Datuk Laksamana is a title given by the Sultan of Siak to maintain security in the Malacca Strait coast. Datuk Laksamana is the option trusted and powerful fully preserve the sea and given the responsibility by the Sultan of Siak to monitor and ensure the safety of enemy attack from the sea, as for the title of Datuk Laksamana consists of four powerful men in Bukit Batu include: Datuk Laksamana Ibrahim, Datuk Laksamana Khamis, Datuk Laksamana Abdullah Saleh, Datuk Laksamana Ali Akbar. 1908 Encik Ali Akbar replace III Bukit Batu with title Laksamana Datuk Setia Diraja, it was agreed by all the captains and the Rich Countries that Encik Ali Akbar as Datuk IV Bukit Batu once the last person who holds Datuk Laksamana. Datuk Laksamana Ali Akbar came to power in 1908-1928. Governments in Bukit Batu is part of the Kingdom of Siak already given rule that was poured in Bab-Al qawa'id, including the limits of the territory of Datuk Laksamana Ali Akbar at that time, besides there are rules and norms that prevail in public life, in the reign Datuk Laksamana Ali Akbar also serves as a judge on duty police Bukit Batu resolve criminal cases occurring in the community at the time. Datuk Laksamana Ali Akbar assisted by the State duty to assist Datuk Laksamana in terms of communal land, crops and also the government, the end of the reign of Datuk Laksamana IV Bukit Batu ends because Parties Netherlands divisive Datuk Laksamana and Sultan Siak, in the end the Siak fully occupied by the Dutch so are able to weaken Bukit Batu.Keywords: History, Government, Datuk Laksamana, Bukit Batu